1997
DOI: 10.1007/bf02767049
|View full text |Cite
|
Sign up to set email alerts
|

Syncope at sleep onset in a patient with nasopharyngeal carcinoma

Abstract: A patient with nasopharyngeal carcinoma developed atypical parapharyngeal-lesion syncope syndrome associated with stereotypical cycles of heart rate variation, which occurred only when he was drowsy before falling asleep. Vagal tone fluctuation is implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The case reports and case series had a mean score of 4.4 (maximum 6, median 5), ranging 3–6. Three studies were deemed of fair quality ( 15 , 16 , 18 ) and 5 of good quality ( 9 , 11 , 12 , 17 , 20 ). The modified NOS scores had a mean score of 6.6 (maximum 9, median 7), ranging 5–8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case reports and case series had a mean score of 4.4 (maximum 6, median 5), ranging 3–6. Three studies were deemed of fair quality ( 15 , 16 , 18 ) and 5 of good quality ( 9 , 11 , 12 , 17 , 20 ). The modified NOS scores had a mean score of 6.6 (maximum 9, median 7), ranging 5–8.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 1,869 unique studies identified by the search strategy, 43 studies were retrieved for full-text review (Figure 1). Of these, 13 met the inclusion criteria and were included in this review (Table 1) (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The studies by Busweiler et al (10) and Jardine et al (6) reported on patients from the same cohort; however, the study by Busweiler et al (10) reported unique data on the body position and upper gastrointestinal symptoms which was not available in the larger, more recent cohort presented in Jardine et al (6).…”
Section: Study Selectionmentioning
confidence: 99%
“…A single case of sleep-onset syncope, attributed to sleep-onset fluctuation in vagal tone, is reported in a patient who had nasopharyngeal carcinoma [332].…”
Section: Miscellaneousmentioning
confidence: 99%